2021
DOI: 10.1016/j.mcpro.2021.100072
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Proteomic and Metabolomic Analysis Reveals Metabolic Phenotype in Mice With Cardiac-Specific Deletion of Natriuretic Peptide Receptor A

Abstract: Metabolomic analysis in mice revealed that natriuretic peptide receptor A (NPRA) is mainly involved in nucleotide biosynthesis and histidine metabolism in cardiac tissues, and in creatine metabolism, TCA cycle and pentose phosphate pathway in the plasma. Furthermore, proteomics revealed that Cox7c, Cox7b, ATP5J2, Uqcr10, and Myh7 play a vital role in the regulation of metabolic pathway. Together, deterioration of NPRA results in metabolic dysfunction involved with a protein and metaboliteinteracting pathway. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In fact, 9 of the top 10 terms are associated with the metabolic process which is in good agreement with our past findings that NPs may play a pivotal role in metabolic functions. [27][28][29] Bubble plots show these metabolic processes in BP bars, the bubble size shows the counts of genes, the number of enriched genes are listed in brackets on the left, and the color of the bubble represents the P-value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, 9 of the top 10 terms are associated with the metabolic process which is in good agreement with our past findings that NPs may play a pivotal role in metabolic functions. [27][28][29] Bubble plots show these metabolic processes in BP bars, the bubble size shows the counts of genes, the number of enriched genes are listed in brackets on the left, and the color of the bubble represents the P-value.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous result showed that there are greatly altered expression profiles in the myocardium tested by RNA-seq 27 and greatly altered metabolic patterns in mice with cardiac-specific deletion of NPRA such as COX, ATP5J2 (mitochondrial membrane ATP synthase), PCr, 2-keto-glutaramic acid (a-KG), etc. 28 Besides, distinguished altered metabolites were also found in HF patients with a remarkably lower cGMP/BNP ratio. 29 However, the molecular mechanism that could account for this observation induced by disabled natriuretic peptide signalling remains to be investigated.…”
Section: Introductionmentioning
confidence: 94%
“…The importance of metabolic reprogramming in the onset and progression of cardiovascular disease has been well characterized (Chang et al, 2021). Since correlation plays an integral part in disease progression, we assume it may be a signi cant cause.…”
Section: Discussionmentioning
confidence: 99%
“…UQCR10 has been involved in the mitochondrial oxidative phosphorylation and myocardial contraction in cardiomyocytes. 37 MrpS28 encodes a mitochondrial ribosomal protein, which is essential for mitochondrial ribosomal assembly, mitochondrial translation and oxidative phosphorylation. 38 NDUFB6 , a mitochondrial gene, plays a major role in reactive oxygen species (ROS) production.…”
Section: Discussionmentioning
confidence: 99%